Pengaruh Penghidaran Pajak Terhadap Kepatuhan Wajib Pajak - HUTAGAOL, ALEXS SUDIBYO; Pintauli, Rolyana Ferinia; Hasibuan, Remista (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
Taxpayer awareness is often a problem when taxpayers are required to pay taxes. This research aims to see whether tax avoidance has an effect on taxpayer awareness. The sample used in this research is IDX BUMN20 (top 10 constituents) contained in the IDX BUMN20 Index Fact Sheet as of December for 5 years 2019-2023. The analysis techniques used are descriptive statistical analysis, classical assumption test, multiple linear regression test and coefficient of determination test. The results of testing the tax avoidance variable toward taxpayer awareness have a positive but not significant effect. The result of the coefficient of determination is 54.2%, this means that the independent variable has an effect on the dependent variable by 54.2%.